Mechanistic Study of a Ru-Xantphos Catalyst for Tandem Alcohol Dehydrogenation and Reductive Aryl-Ether Cleavage - Chmely, S; Kim, S; Ciesielski, P; Jimenez-Oses, G; Paton, R; Beckham, G (2013)
We employ density functional theory (DFT) calculations and kinetics measurements to understand the mechanism of a xantphos-containing molecular ruthenium catalyst acting on an alkyl aryl ether linkage similar to that found in lignin to produce acetophenone and phenol. The most favorable reaction pathway suggested from DFT is compared to kinetics measurements, and good agreement is found between the predicted and the measured activation barriers. The DFT calculations reveal several interesting features, including an unusual 5-membered transition state structure for oxidative insertion in contrast to the typically proposed 3-membered transition state, a preference for an O-bound over a C-bound Ru-enolate, and a significant kinetic preference for the order of product release from the catalyst. The experimental measurements confirm that the reaction proceeds via a free ketone intermediate, but also suggest that the conversion of the intermediate ketone to acetophenone and phenol does not necessarily require ketone dissociation from the catalyst. Overall, this work elucidates the kinetically and thermodynamically preferred reaction pathways for tandem alcohol dehydrogenation and reductive ether bond cleavage by the ruthenium-xantphos catalyst. © 2013 American Chemical Society.